Peculiarities of Amateur Theatres Functioning in Penitentiary Institutions: a Historiographical Discourse - Iudova-Romanova, Kateryna; Borko, Ihor; Matuzko, Оleksandr (Вісник Київського національного університету культури і мистецтв. Серія: Сценічне мистецтво, 2024)
The purpose of the study is to analyse and systematise the identified scientific studies that examine the role and features of amateur theatres activities in penitentiary institutions. Research methodology. To achieve this purpose, a combination of the following methods was used: literature analysis to systematise scientific sources, which allowed us to identify key trends and concepts; meta-analysis to study the results of previous studies, which helped to identify general patterns and relationships between different aspects of the role of theatres in penitentiary institutions; systematisation, which helped to summarise the results of previous studies to identify the needs for further research. The novelty of the study lies in the fact that the authors have collected and systematised articles and monographs by foreign and Ukrainian authors in order to scientifically comprehend the potential humanistic possibilities of theatre in the system of socio-cultural communication practices. Conclusion. The analysis of foreign works by foreign researchers shows that the topic of the role and peculiarities of amateur theatres in penitentiary institutions is interesting and relevant for many world countries. This demonstrates the wide interest of the scientific community in the possibilities of theatre practice in the context of prisons and the criminal justice system in general. A considerable number of publications address theatre in prisons in the context of combating racism, systems of oppression and other forms of social inequality, which demonstrates the diversity of research topics and points to the potential of theatre programmes to support human rights and create a space for prisoners to express themselves and their feelings. The identified sources argue that theatre practices can promote empathy and complicity among participants in prisons, which certainly increases the possibilities for changing communication and interaction in prison and improving the psychological state of prisoners. The authors have ...